Børn i udsatte positioner i implementeringen af Den styrkede pædagogiske læreplan: Et pædagogisk dilemma flytter med - Tegtmejer, Thyge; Langerhuus, Janni Tofte; Jerg, Kim; Nielsen, Kaare Werner; Huusfeldt, Morten; Ellebæk, Lasse Stenmann (Tidsskrift for Professionsstudier, 2021)
The strengthened pedagogical curriculum is by various parties presented as a movement away from a narrow focus on educational output with measurements of children’s progress and capabilities. Because of this, accompanying legal frameworks contains a distancing to criticized time-consuming documentation requirements set for day care professionals’ work. However, before as well as after the legislative change, municipal administrations of day care have an obligation to secure measures towards children in vulnerable positions. In this study, we examine the implementation of the strengthened pedagogical curriculum in four municipalities, with a focus on municipal decisions in regards to children in vulnerable positions. The main conclusion is that all municipalities choose to maintain tools to measure and describe all children’s learning and progress, and that this is done with reference to children in vulnerable positions. The study discusses a basic pedagogical dilemma between, on the one hand, making individual children’s challenges visible – and thus risking that children will be met by focus at their deficiency. And, on the other hand, refraining from pointing out challenges – and, because of that, risking that special needs will not be met and competencies needed in school and life will not be sufficiently developed.